‘English only’ to ‘English for all’ - a new Paradigm Shift - Shrestha, Amul (Journal of Business and Social Sciences, 2021)
Due to globalisation and the influence of the historical events like colonisation made English language as a global lingua franca and the language comprising highest speakers in the world. Because of its indomitable nature, the languages of the world got influenced. Thus, English as a second or foreign language (ESL/EFL) might be the counterpart to any other languages belonging to any nations. Consequently, bi-multilingualism has been a new paradigm shift from monolingual era opening the horizon of divergent linguistic features. This paper provides an ample space to discuss about the implication of multilingualism eradicating the era of monolingualism and diversity management in ELT classroom in academia. This article articulates about the new innovative ideas for creating the languages of same standard in the society, without any biasness, releasing the more luring path for cultural connection.  And yet a gap has been left behind to plan, promote and produce for the further researches in this field.